Competitiveness and its determinants: a systemic analysis for developing countries - Medeiros, Victor (2020)
This paper seeks to make a comparative and econometric analysis of competitiveness in developing countries, identifying its determinants and sources of variation. It uses the data envelopment analysis methodology to generate measures of competitiveness. The determinants of competitiveness are obtained through a Tobit model based on the systemic competitiveness approach. As average competitiveness is low, the main results show that resource allocation could be improved in many of the countries in the sample. In addition to business factors such as innovation and the sophistication of the business environment, structural aspects such as market size and quality of demand, along with systemic factors such as infrastructure, health, education, workforce training and the macroeconomic environment, are all important for enhancing the competitiveness of emerging countries.